2015
DOI: 10.1259/bjr.20140687
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy with helical TomoTherapy for medically inoperable early stage primary and second-primary non-small-cell lung neoplasm: 1-year outcome and toxicity analysis

Abstract: The authors Alban Lovis and Oscar Matzinger contributed equally to this article.Objective: This study investigated the effectiveness of stereotactic body radiotherapy with helical TomoTherapy (T-SBRT) for treating medically inoperable primary and second-primary early stage non-small-cell lung neoplasm (SPLN) and evaluated whether the movement of organizing pneumonia (OP) within the irradiation field (IF) can be detected via analysis of radiological changes. Methods: Patients (n 5 16) treated for 1 year (2011-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…So, the application of MVCT can catch the change of tumor volume to achieve adaptive radiotherapy (31). Previous studies also confirmed the safety and effectiveness of tomotherapy for SBRT (32)(33)(34).…”
Section: Discussionsupporting
confidence: 55%
“…So, the application of MVCT can catch the change of tumor volume to achieve adaptive radiotherapy (31). Previous studies also confirmed the safety and effectiveness of tomotherapy for SBRT (32)(33)(34).…”
Section: Discussionsupporting
confidence: 55%
“…Owing to the aforementioned disadvantages of HT compared with other stereotactic treatments in this setting, HTT is slow to be adopted in clinical practice, and few studies-often evaluating small series of patients with inhomogeneous characteristics and short FU-are available in the recent literature [9][10][11][12][13][14][15][16] (Table 4). Several points can be gleaned from this study, which to our knowledge is one among the largest series addressing the use of HTT in the treatment of lung lesions.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 While dosimetric findings have shown that such capabilities can potentially translate into the delivery of an increased tumour dose with doses to normal tissues decreased compared with other techniques, 7,8 only a limited number of patients were included in recent studies that have addressed the feasibility of hypofractionated or ablative radiotherapy (RT) regimens for lung tumours treated with HT. [9][10][11][12][13][14][15][16] Reasonable arguments might be advocated for its slow adoption in the clinical practice in this setting: during HT it is not only the tumour and the MLC that are moving but also the radiation source and couch, which can maximize the breathing interplay effect (i.e. difference between planned and delivered absorbed doses that arises from a mismatch between the tumour and the MLC because of motion).…”
Section: Introductionmentioning
confidence: 99%
“…In the study published by Ricardi et al [30], the most frequent side effects observed also included skin reactions like erythema. Conversely, in the same clinical series, sub-acute/late toxicity was quite uncommon and included two cases of grade C3 pneumonitis [30,31]. Onishi et al [3] reported a rib fracture and a grade 3 dermatitis in four (4.6 %) and three patients (3.4 %), respectively.…”
Section: Toxicity Associated With Sbrtmentioning
confidence: 93%